Long-term mortality risks associated with mild anaemia in older persons: The Busselton health study - Chalmers, K.; Knuiman, M.; Divitini, M.; Bruce, D.; Olynyk, John; Milward, E. (Oxford University Press, 2012)
Background: Up to 25% of older people in the USA and other Western countries are anaemic by World Health Organization (WHO) criteria. The objective of this study was to examine the long-term relationships of haemoglobin concentration with all-cause and cause-specific mortality in a community-based sample of Australian adults surveyed in 1978. Methods: A community survey of 2,194 adults aged 40+ years in Busselton, Western Australia in 1978 with mortality follow-up to 2001. Cox regression models were used to investigate the relationships of haemoglobin as a continuous measure and anaemia by WHO criteria (women <12 g/dl (7.5 mmol/l); men <13 g/dl (8.1 mmol/l)) with all-cause, cardiovascular and cancer mortality. Results: Anaemia was predominantly mild (>10 g/dl) and normocytic. There was an increased risk of death from all causes and from cancer for men with low haemoglobin. Cancers were predominantly of the prostate and genito-urinary organs, and to a lesser extent the gastrointestinal tract. There was no increased risk of all cause or cancer death in women. Conclusion: Mild, normocytic anaemia is associated with survival reductions in middle-aged and older men, where it often occurs with prostate, gastrointestinal and other cancers, and should be investigated to exclude treatable causes.